Safety of Annona muricata Extract Supplementation for Colorectal Cancer Patients - Lili Indrawati; Purwantyastuti Purwantyastuti; Murdani Abdullah; Ingrid S Surono; Ibrahim Basir (The Indonesian Society for Digestive Endoscopy, 2016)
Background: People have used Annona muricata leaves traditionally as tea drinks. Traditional use of A. muricata leaves is as an infusion which is closed to water extract. The potential health benefit of A. muricata tea leaves that is traditionally used for maintaining health which lately is being used by cancer patients. Therefore it is urgent to verify the safety of A. muricata leaves extract. Method: A randomized double blind placebo controlled trial was conducted on 30 colorectal cancer out patients who had undergone primary tumor resection. Twenty eight subjects completed the study, divided into two groups, namely ethanol-soluble fraction of A. muricata leaves water extract (ESFAM) (n = 14), and placebo (n = 14) for 8 weeks. Peripheral blood samples were withdrawn from subjects by venipuncture at baseline and at the end of the study period.Results: The effect on bone marrow can be considered to be safe. The measure in indices of organs function, i.e liver and kidney also showed similar results and within normal range after supplementation. The dose given to the subjects is safe and highly tolerable, as shown by very few (6.7%) of patients complained intolerable adverse effects. Conclusion: This study indicates the safety of ESFAM supplementation.